Effect of conical pin arrangement on heat transfer efficiency of a free convective solar air heater - Gilani, S.E. (Universiti Malaysia Pahang, 2016)
The artificial roughnesses on absorber plate have been known to enhance the performance of the solar air heater under forced convection. The objective of this paper is to study the effect of conical pin arrangement on the heat transfer enhancement of free convective solar air heater. The conical pins were arranged in-line and in staggered arrangement with the pitch-to-height ratio of eight. The height of the conical pin was fixed at 0.2 cm. The measurement results revealed that the use of conical pin on the surface of absorber plate helped to improve the overall efficiency of the solar air heater. The staggered arrangement of the conical pins performed better compared to the case of the in-line arrangement. The performance of the solar air heater with the staggered arrangement was 42 higher than that of the flat absorber plate with no pins at 435 W/m2 while the in-line arrangement showed an increase of 28. Hence, the use of the artificial pin roughening technique with the staggered arrangement is recommended in the free convection solar air heater. Â© Universiti Malaysia Pahang.